Determining The Effects of Salicylic Acid Applications on High Temperature Stress in Narince Grape Variety - Neval Topcu Altıncı; Rüstem Cangi; Deniz Üstün (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Plants are constantly exposed to adverse conditions in their environment, which may occur in different ways, limiting their growth. These negative states that affect and / or prevent growth, development and metabolism in plants are called stress. Salicylic acid (SA) is a hormone-like substance commonly found in plants and is now accepted to play an important role in regulating plant growth and development. Salicylic acid also increases the tolerance of plants under abiotic stress conditions such as salinity, high and low temperature, water, heavy metal, frost and drought stress. This study is one of the important white wine grape varieties belonging to Turkey's Narince grape varieties growing in Tokat made widely used. Salicylic acid (SA) was applied to the plants in 4 different doses (0, 0.5, 1.0, 1.5 µmol l-1) before high temperature stress to be applied and they were exposed to high temperature for 12 hours at 40°C in the growth chamber. At the end of the 21 days after the stress application, shoot length (cm), fresh -dry shoot and root weights (g) were taken in order to follow the plant growth from the plants. Proportional water content (%), Ion flow (%) to reveal the effect of salicylic acid and the cell membrane damage rate (%) was calculated.